Comparison of the Effects of Anticardiolipin Antibodies from Patients with the Antiphospholipid Syndrome and with Syphilis on Platelet Activation and Aggregation - Campbell, Andrew L; Pierangeli, Silvia S; Wellhausen, Samuel; Harris, Nigel E (Thrombosis and Haemostasis, 1995)
Anticardiolipin antibodies (aCL) are induced both in the Antiphospholipid Syndrome (APS) and syphilis, but thrombosis, thrombocytopenia, and pregnancy loss occur only in the APS. Differences in specificity and function of aCL antibodies might explain clinical differences between APS and syphilis. This study compared the effects on platelet activation and aggregation of affinity purified IgG anticardiolipin antibodies from 6 patients with the APS (IgG-APS) and 5 patients with syphilis (IgG-syph). Platelet aggregation was studied by aggregometry and platelet activation by flow cytometry. In the presence of low concentrations of thrombin, ADP, or collagen, all 6 IgG-APS samples induced platelet aggregation and activation, but none of the IgG-syph samples had this effect. In the absence of platelet agonists, only 3 of 6 IgG-APS caused platelet aggregation and none caused platelet activation; IgG-syph had no effect. The IgG-APS samples but not IgG-syph bound phosphatidylserine by ELISA. We conclude that polyclonal antibodies specific for phosphatidylserine may induce platelet activation and aggregation in the presence of low concentrations of platelet agonists.